Harry Potter and the Half-Blood Prince - Rowling, J. K.; GrandPré, Mary (New York, NY : Arthur A. Levine Books, 2005)
Sixth-year Hogwarts student Harry Potter gains valuable insights into the boy Voldemort once was, even as his own world is transformed by maturing friendships, schoolwork assistance from an unexpected source, and devastating losses.
"Year 6"--Spine.
Sequel to: Harry Potter and the Order of the Phoenix.
Sequel: Harry Potter and the deathly hallows.
Keywords: Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Fiction